2022
DOI: 10.3390/app12031180
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Shear Band in Plane Strain Compression of Naturally Structured Clay with a High Sensitivity

Abstract: The formation of the shear band is associated with the failure of soil. However, there has been relatively little investigation on the evolution of shear bands in naturally structured clay with a high sensitivity. In this study, undrained plane strain compression tests, digital image correlation (DIC) analyses, and scanning electron microscopy (SEM) tests were performed to investigate the characteristics of shear bands in naturally structured clay. The basic mechanical properties and stress–strain relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Both figures indicate that the shear band only developed at a very late stage (axial strain 7.0%-9.0%). This agrees well with the findings in Liu et al [38] that localization increases with higher confining pressures under the plane strain condition. The plot of gradient along ρ axis F 11 (Figure 15) shows that the middle expansion started from an axial strain of 1.0%-3.0%.…”
Section: Dense Specimen At Confinement Of 20 Kpa (Test 121304d)supporting
confidence: 93%
“…Both figures indicate that the shear band only developed at a very late stage (axial strain 7.0%-9.0%). This agrees well with the findings in Liu et al [38] that localization increases with higher confining pressures under the plane strain condition. The plot of gradient along ρ axis F 11 (Figure 15) shows that the middle expansion started from an axial strain of 1.0%-3.0%.…”
Section: Dense Specimen At Confinement Of 20 Kpa (Test 121304d)supporting
confidence: 93%
“…The result concluded that the orientation of shear band completely depend on characteristics behavior of granular soil under the sample is subjected. Liu et al (2022) [13] performed three methods compression test, digital image correlation and scanning electron microscopy to study the development of shear band in sensitive soil under low to high confining pressure. It was observed that a large number of shear band emerges at a high confining pressure, which changes the internal properties of soil.…”
Section: Introductionmentioning
confidence: 99%